Prospective registration of symptoms and times to diagnosis in children and adolescents with central nervous system tumors: A study of the Swedish Childhood Cancer Registry - Rask Olof; Nilsson Fredrik; Lähteenmäki Päivi; Ehrstedt Christoffer; Holm Stefan; Sandström Per-Erik; Nyman Per; Sabel Magnus; Grillner Pernilla; Swedish Childhood CNS Tumor Working Group(VCTB) (WILEY, 2022)
Background: The elapsed time taken to diagnose tumors of the central nervous system in children and adolescents varies widely. The aim of the present study was to investigate such diagnostic time intervals at a national level in Sweden as they correlate with clinical features.
Methods: Data prospectively accumulated over a 4-year period in the Swedish Childhood Cancer Registry from patients aged 0-18 years were pooled, and diagnostic time intervals were analyzed considering tumor location, tumor type, patient age and sex, initial symptoms, and clinical timelines. All six pediatric oncology centers in Sweden contributed to collection of data. Time points for calculating the total diagnostic interval (TDI) defined as the time from symptom onset to diagnosis were reported in 257 of 319 patients (81%).
Results: The time from symptom onset to the first healthcare consultation, median 2.6 weeks, did not vary significantly between patients categorized according to tumor type or location. The median TDI was 8.3 weeks for the 4-year study period. Patients with optic pathway glioma (TDI 26.6 weeks), those with tumors of the spinal cord (TDI 25.9 weeks), and those with midline tumors (TDI 24.6 weeks) had the longest lead times. Additionally, older age, too few initial symptoms, and seeking initial redress outside an emergency ward were factors associated with a longer time to diagnosis.
Conclusion: This study identified several factors associated with delayed diagnosis of central nervous system tumors among Swedish children and adolescents. These novel data ought to help direct future efforts toward clinical improvement.